Patients' perceived health service needs for osteoarthritis (OA) care: a scoping systematic review - Papandony, M.; Chou, L.; Seneviwickrama, M.; Cicuttini, F.; Lasserre, K.; Teichtahl, A.; Wang, Y.; Briggs, Andrew; Wluka, A. (Elsevier, 2017)
OBJECTIVE: To identify and synthesise evidence regarding patients' perceived health service needs related to osteoarthritis (OA). DESIGN: A comprehensive systematic scoping review of MEDLINE, PsycINFO, EMBASE and CINAHL (1990-2016) was performed to capture information regarding patient perceived health service needs related to OA. Risk of bias and quality of included articles were assessed. Relevant data were extracted and collated to provide a systematic review of the existing literature. RESULTS: Of the 1384 identified manuscripts, 21 were relevant to areas of patient perceived need, including needs related to medical care, pharmacologic therapy, physiotherapy and exercise therapy and alternative medicine. Key findings included (1) Symptom control drove the need for both conventional and complementary services. (2) An individualized relationship was sought with a practitioner knowledgeable in OA care and who adopted a holistic approach, whether providing conventional or alternative therapies. (3) Medications were required to obtain symptomatic relief, with use tempered by recognition of potential side effects and financial cost. (4) The need for allied health services was recognised, although patient and system issues were barriers to uptake. (5) Patient's attitudes towards joint replacement, orthoses and physical aids were influenced by patient preferences and previous healthcare experiences. CONCLUSION: Patient perceived needs are similar to those suggested by clinical guideline recommendations. Better aligning patient perceived needs with healthcare requirements may improve OA outcomes and optimise healthcare system utilisation.